Stress in sport situations experienced by people who practice karate - Sterkowicz, S.; Blecharz, J.; Sterkowicz-Przybycien, K. (Archives of Budo, 2012)
Background and study aim: Sport situations are difficult. Stress can be a factor which decreases the quality of sports performance, especially during competition. The aim of this study is to identify situations which generate the highest stress levels in karate contestants. Material and methods: Polish National Kyokushin team members (n=22) participated in the study. Questions concerning training and competitions were answered on a 10 - point scale. Cronbach alfa for questionnaire items were 0.84-0.97. Stress demand level was determined by sports motivation questionnaire. Mean values of males and females were compared by non-parametric tests (p<0.05). Results: Competitions generated higher stress than training. Importance of competition and presence of audience increased stress intensity. Quality of fighting activities modified stress intensity. Stress intensity at the end of karate match remained lower in men than women. Stress during the first selection match and semi-final fight exceeded athletes` general demand for stress. Stress intensity was lower than the demand for stress during tactical and technical training, free of audience. The dissonance between stress intensity and demand for stress in women in final fights, against stronger opponent, exposed them to psychological discomfort. Conclusions: Psychological and tactical preparations correlate. This manifests by development and realization of a fight plan and reaction to unexpected situation. Differences in reactions between men and women in stressful situations suggest the need for individual approach to training process and at each stage of competition.